Analysis of Factors Including Pulmonary Tuberculosis in Diabetes Mellitus Patients - Marhamah Marhamah; Basri Aramico Ib; Meutia Zahara (GLOBAL HEALTH SCIENCE GROUP, 2026)
The syndemic between Pulmonary Tuberculosis (TB) and Diabetes Mellitus (DM) is a public health challenge because DM can weaken the immune system and poor glycemic control facilitates infection by Mycobacterium tuberculosis. As the prevalence of DM in Indonesia increases, identifying risk factors that contribute to the incidence of TB in DM patients becomes important. This study aims to analyze the relationship between nutritional status, glycemic control, income level, education level, and access to health services with the incidence of pulmonary TB in DM patients. The study used an observational analytical design with a cross-sectional approach conducted at Tgk. Chik Ditiro Sigli Regional Hospital from June–September 2025 with a sample of 277 DM patients selected through purposive sampling. Data were collected using mixed methods, namely secondary data from medical records for TB status, nutritional status, and glycemic control and primary data through questionnaires for income and access to health services using the Cronbach’s Alpha method with a value of ≥0.70.The results showed that the majority of respondents did not have pulmonary TB (75.09%), but the majority had poor nutritional status (68.95%) and most had controlled glycemic control (71.12%). In addition, more than half of respondents had incomes below the Provincial Minimum Wage (56.68%) and about half had poor access to health services (50.54%). The analysis showed a significant association between poor nutritional status (AOR=2.5; 95% CI=1.17–5.39), uncontrolled glycemic control (AOR=4.5; 95% CI=2.43–8.68), income <UMP (AOR=1.9; 95% CI=1.02–3.85), and poor access to health services (AOR=3.2; 95% CI=1.65–6.30) with the incidence of pulmonary TB in DM patients,